2013
DOI: 10.15376/biores.8.2.2950-2966
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Activated Carbon from Apple Waste by Microwave-Assisted Phosphoric Acid Activation: Application in Methylene Blue Adsorption

Abstract: Activated carbons (ACs) prepared from apple pulp and apple peel with phosphoric acid as an activation agent under microwave radiation were investigated. The effects of microwave radiation power and time on the adsorption capacities of the ACs were studied. The optimum AC preparation condition was identified by comparing the MB adsorption capacities of the produced ACs. The obtained results show that the microwave radiation power and time had strong effects on the adsorption capacities. Relative to conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 21 publications
0
40
1
3
Order By: Relevance
“…Hesas et al [28] reported the highest adsorption (94.6%) among all the studies. The reason for this could be due to the relatively smaller surface area of activated carbon because it is obvious that a higher surface area leads to a higher adsorption efficiency [33].…”
Section: Ftir Analysismentioning
confidence: 86%
See 1 more Smart Citation
“…Hesas et al [28] reported the highest adsorption (94.6%) among all the studies. The reason for this could be due to the relatively smaller surface area of activated carbon because it is obvious that a higher surface area leads to a higher adsorption efficiency [33].…”
Section: Ftir Analysismentioning
confidence: 86%
“…Many studies have been done on the removal of dye molecules from aqueous solutions by activated carbon; however, most of them were unable to remove dye molecules completely (100%) in a short time period [28][29][30][31][32]. Hesas et al [28] reported the highest adsorption (94.6%) among all the studies.…”
Section: Ftir Analysismentioning
confidence: 99%
“…The PSD is one of the important material properties, which determines the fraction of the total pore volume accessible to molecules of a given size and shape. 20 Total pore volumes (0.842 cm 3 g −1 for CAC and 0.830 cm 3 g −1 for MAC) are presented in Table 3 are quite comparable but CAC has significantly bigger micropore pore volume (0.488 cm 3 g −1 ) than MAC (0.354 cm 3 g −1 ). Therefore, the higher gas adsorption of CAC is due to its larger specific surface area mainly contributable to micropores.…”
Section: Psd and Volume Of The Carbonsmentioning
confidence: 92%
“…Apple pulp and apple peel  Modified microwave oven was used  Furnace was used during the activation process.  Activation agent: phosphoric acid  The highest removal of methylene blue was 94.6% and 87.2% for pulp-based, and peel-based activated carbon [52].  BET surface area showed the highest value (1552 m 2 /g) in apple peel based activated carbon if compared to pulp based (1103 m 2 /g).…”
Section: Elaeagnus Stonementioning
confidence: 99%